Analysis of the Effect of Firm Size, Profitability, Solvency, and Size of Public Accounting Firms on Audit Delay in Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange Period 2012-2016 - Eka Wulan Pratika Br. Sihite Br. Sihite (International Journal of Applied Finance and Business Studies, 2020)
The objective of this research is to know the influence between firm size, profitability, solvency, auditor firm size to audit delay in consumer good companies that are listed in Indonesia Stock Exchange in 2012 up to 2016. This research used secondary data which can be accessed through the website of the Indonesia Stock Exchange (www.idx.co.id). The population for this research is 13 consumer good companies with the food and beverage sub sector, and for the sampling method, purposive sampling is used. With this method, 11 companies are acquired as a sample with 5 years of observation period. Thus the sum of this research is 55 analysis units. Then firm size, profitability, solvency, auditor firm size, and audit delay are tested using multiple linear regression analysis using SPSS 20. Before being conducted using the regression test, it is examined using the classical assumption tests. The result of this research shows that all of the independent variables has significant influence on audit delay simultaneously. Partially, auditor firm size has significant and negative influence on audit delay. Meanwhile, firm size, profitability, solvency have no significant influence to audit delay.